Español - Sacristan Moraleda, Marcos; Ibañez, Jaime; Lázaro, Jesús (Jornada de Jóvenes Investigadores del I3A, 2024)
This study investigates the impact of transcutaneous spinal stimulation on autonomic nervous system activity by analyzing heart rate variability. Significant differences in parasympathetic markers were found between control and stimulation conditions, suggesting effects of stimulation on autonomic nervous system activity.